Court of the Hemispheres - Treasure Island, Golden Gate International Exposition on San Francisco Bay (Stanley A. Plitz Company)
The terminus of the mile-long main esplanade of this World's Fair is the Court of the Hemispheres with its imposing gateway to the Theatre of the Sky. Structural Pageantry that combines the most interesting features of color and architecture in the Occident and the Orient are seen at the Golden Gate International Exposition, on Treasure Island in San Francisco Bay. Brilliant-hued murals, walls in golden designs, waving banners and giant globes that reveal the continents in colored relief, will surround the fountains and gardens of the court.